A 481-meter-high landslide-tsunami in a cruise ship–frequented Alaska fjord - Dan H. Shugar; Katherine R. Barnhart; Mira Berdahl; Jacqueline Caplan-Auerbach; Göran Ekström; Aram Fathian; Marten Geertsema; Stephen P. Hicks; Bretwood Higman; Erin K. Jensen; Ezgi Karasözen; Patrick Lynett; et al. (Science, 2026)
Early in the morning of 10 August 2025, a >64 × 10 6 –cubic meter landslide struck Tracy Arm fjord in Alaska. The landslide was preconditioned by glacial retreat caused by climate change. The resulting 481-meter runup megatsunami followed an initial 100-meter-high breaking wave traveling at >70 meters per second. The landslide was preceded by several days of microseismicity, which increased in rate and magnitude until ~1 hour before failure. The landslide produced globally observed long-period seismic waves equivalent in size to a moment magnitude 5.4 earthquake. A long-period (~66 second) global seismic signal, produced by a landslide-induced seiche trapped within the fjord, persisted for up to 36 hours, the second time a days-long seiche had thus been observed. With fjord regions increasingly visited by cruise ships, and climate change making similar events more likely, this unanticipated, near-miss event highlights the growing risk from landslides and tsunamis in coastal environments.